Stroke induces long-lasting deficits in the temporal fidelity of sensory processing in the somatosensory cortex - Sweetnam, Danielle A (Nature Publishing Group, 2013)
Recovery from stroke is rarely complete as humans and experimental animals typically show lingering deficits in sensory function. One explanation for limited recovery could be that rewired cortical networks do not process sensory stimuli with the same temporal precision as they normally would. To examine how well peri-infarct and more distant cortical networks process successive vibro-tactile stimulations of the affected forepaw (a measure of temporal fidelity), we imaged cortical depolarizations with millisecond temporal resolution using voltage-sensitive dyes. In control mice, paired forepaw stimulations (ranging from 50 to 200 milliseconds apart) induced temporally distinct depolarizations in primary forelimb somatosensory (FLS1) cortex, and to a lesser extent in secondary FLS (FLS2) cortex. For mice imaged 3 months after stroke, the first forepaw stimulus reliably evoked a strong depolarization in the surviving region of FLS1 and FLS2 cortex. However, depolarizations to subsequent forepaw stimuli were significantly reduced or completely absent (for stimuli ⩽100 milliseconds apart) in the FLS1 cortex, whereas FLS2 responses were relatively unaffected. Our data reveal that stroke induces long-lasting impairments in how well the rewired FLS1 cortex processes temporal aspects of sensory stimuli. Future therapies directed at enhancing the temporal fidelity of cortical circuits may be necessary for achieving full recovery of sensory functions.